Proteção social e o direito a convivência familiar de crianças e adolescentes em acolhimento em João Pessoa - Paraíba - Furtado, Antonia Gomes (2013)
The present study addresses the family reintegration processes occurring in the host Units of the municipality of João Pessoa. The main objective of this work is to analyze the process of Family Reintegration of children and adolescents received at the institution, identifying aspects that contribute or hamper the right to effective family and community coexistence. Are used qualitative data obtained through interviews with children and adolescents s who were reinstated to the family context and to their families. The work stands out, at first, social protection, emphasizing the family as one of the main focuses of this protection. Discusses the support to children and adolescents in Brazil, with emphasis on the institutionalization and family reintegration approaches vis-à-vis the Social Assistance policy. From this political context, bibliographical and documental analysis and research data, the study focuses on the process of family reintegration of children and adolescents in situations of institutional reception and in challenges to guarantee the right to family and community life. The survey found advances and continuities in the context of institutional childcare. The families of the children and adolescents interviewed have their condition of social vulnerability, expressed through violence, and family conflict, chemical dependency, street, unsanitary conditions of housing, which resulted in the reception of children and adolescents. The process of reunification was experienced from the changes that have taken place in this context and the strengthening of the family and community ties. Social protection is a fundamental instrument for the guarantee of the right to family living.